2019
DOI: 10.1111/jcmm.14530
|View full text |Cite
|
Sign up to set email alerts
|

Low‐intensity aerobic exercise improves cardiac remodelling of adult spontaneously hypertensive rats

Abstract: We evaluated the influence of aerobic training on cardiac remodeling in untreated spontaneously hypertensive rats (SHR). Four experimental groups were used: sedentary (W‐SED, n=27) and trained (WEX, n=31) normotensive Wistar rats, and sedentary (SHR‐SED, n=27) and exercised (SHR‐EX, n=32) hypertensive rats. At 13 months old, trained groups underwent treadmill exercise five days a week for four months. Statistical analysis: ANOVA or Kruskal‐Wallis. Exercised groups had higher physical capacity. Hypertensive gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 15 publications
2
16
0
Order By: Relevance
“…Because the progress of hypertension is normally followed by cardiac remodeling (Cohn et al, 2000; Duchatsch et al, 2020; Han et al, 2015; Hernandez et al, 2013; Pagan et al, 2015; Pagan et al, 2019; Rossoni et al, 2011), this present study evaluated the structural and functional changes determined by hypertension through the echocardiographic analysis and confirmed some previous results recently found by our group and others (Duchatsch et al, 2020; Han et al, 2015; J. Li et al, 2019) that SHR, even at 5 months, had higher LV relative wall thickness and increased LVMI, which can be induced by pressure overload (Bernardo et al, 2010). In fact, this increased LV RWT probably contributed to the reduced internal diameter during systolic and diastolic periods, as observed in these rats.…”
Section: Discussionmentioning
confidence: 99%
“…Because the progress of hypertension is normally followed by cardiac remodeling (Cohn et al, 2000; Duchatsch et al, 2020; Han et al, 2015; Hernandez et al, 2013; Pagan et al, 2015; Pagan et al, 2019; Rossoni et al, 2011), this present study evaluated the structural and functional changes determined by hypertension through the echocardiographic analysis and confirmed some previous results recently found by our group and others (Duchatsch et al, 2020; Han et al, 2015; J. Li et al, 2019) that SHR, even at 5 months, had higher LV relative wall thickness and increased LVMI, which can be induced by pressure overload (Bernardo et al, 2010). In fact, this increased LV RWT probably contributed to the reduced internal diameter during systolic and diastolic periods, as observed in these rats.…”
Section: Discussionmentioning
confidence: 99%
“…Both SHR groups had higher RT and -dT/dt than their respective controls. RT is mainly related to the myocardial collagen content ( Matsubara et al, 1997 ), which is increased in the senescent SHR ( Cezar et al, 2015 ; Pagan et al, 2015 , 2019 ). The –dT/dt values are dependent on the diastolic Ca 2+ removal from cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects of physical exercise during persistent pressure overload are not completely understood and both beneficial and adverse effects have been described ( Schultz et al, 2007 ; da Costa Rebelo et al, 2012 ; Locatelli et al, 2017 ; Schreckenberg et al, 2017 ). We have previously observed that low intensity aerobic exercise improves diastolic function by attenuating myocardial fibrosis and metalloproteinase-2 activity ( Pagan et al, 2015 , 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…We observed a large variety in overall study characteristics ( Supplementary Materials Table S1 ). The majority of studies used rodents: either mice (12 articles) [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ] or rats (6 articles) [ 49 , 50 , 51 , 52 , 53 , 54 ]. Other species included swine (n = 3) [ 55 , 56 , 57 ], rabbit (n = 1) [ 58 ] and guinea pig (n = 1) [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Given the pooled and separate effect of hemodynamic models on increased E/e’ ratio but lack of effect on E/A and E-wave, e’ seems to represent the most reliable change in LVDD/HFpEF. Indeed, Zhong et al [ 43 ], Pagan et al [ 51 ] and Sam et al [ 42 ] show a decreased e’ (3/5 comparisons). Clinically, e’ also has the highest reproducibility and a consistent association with CVD outcomes [ 62 ].…”
Section: Discussionmentioning
confidence: 99%